The Effect of Question Answer Relationship Strategy on Students’ Reading Comprehension of Narrative Text at VIII Grade of SMP Muhammadiyah 4 Giri - Anggun, Diajeng (Jetlal, 2017)
Question-Answer Relationships (QAR) is a reading comprehension strategy developed to clarify how students approach the tasks of reading texts and answering questions. This study aimed to know how the significant effect and the effects of Question-Answer-Relationship strategy (QAR) on the reading comprehension of narrative text students at eight grade SMP Muhammadiyah 4 Giri. The researcher took 48 students as the sample. They grouped into two classes, one of experiment group VIII A that consist of 24 students and VIII B as control group that also consist of 24 students. The design of the study was Quasi Experimental Design. The instrument used collect data was reading test to set scores of students’ reading comprehension. In this research, there are five procedures of research design that was giving pre test, giving treatments, giving post test, analyzing the data using t-test formula and wrote the hypothesis. The research finding showed that this strategy was effective to teach reading for eight grade at SMP Muhammadiyah 4 Giri. The students’ average score in pre test between experimental and control group was 57.50 and 58.54. The score improved in post test. The significant value of experimental group was 0.00 it was lower than the level of significant at 0.005. Based on the hypothesis result, there is significant different between experimental and control group. The researcher concluded that QAR strategy could improve students’ reading comprehension especially in narrative text. By using this strategy, students could learn by working in groups. In general, the use of QAR strategy to teach reading comprehension was quite good. Students appeared more active and cooperative in discussion section. Three are suggestions are provided. The first, the English teacher is recommended to use QAR as an effective additional strategy in teaching reading narrative text and to avoid monotonous activities in the class. The second, for the students is the researcher hopes the use of QAR can be used to alternate and motivate students in reading and can be used to maximize teaching and learning process in the class. The third, for the next researcher was who wants to conduct a research using QAR were recommended to conduct this research in different areas and levels.